The impact of knowledge management processes on the development of intellectual capital: A survey study on a sample of private colleges (Entrepreneurship Journal for Finance and Business, 2024)
The research aims to review the impact of knowledge management of the process on development in intellectual capital, and by referring to what has been dealt with in related research and studies, and on its basis, a hypothetical chart was formulated to clarify the influence relationships between the variables investigated, and knowledge management was taken, which is considered an independent variable in its dimensions (knowledge discovery, Possession of knowledge, sharing knowledge) and intellectual capital as a dependent variable with its dimensions (employee skills, innovation and innovation, employee morale). The sample contained (120) teachers from a number of private colleges in Baghdad, and The researcher found that Intellectual capital development is positively and morally impacted by the knowledge management process.